Study of A Phenomenon STT (Spin Transfer Torque) on the Material La0.7Sr0.3MnO3 Shaped Nanowire Using Micromagnetic Simulation - Rohman, Lutfi; Musyarofah, L.; Purwandari, Endhah (Jurnal ILMU DASAR, 2017)
STT (Spin Transfer Torque) can be referred to as a process of manipulation and control of spin current in the field of spintronics. When the material is ferromagnetic nanowire La0.7Sr0.3MnO3injected currents will move the domain wall with accompanying changes of spin currents. In mikromagnetik simulation shows that the application is capable of producing flow velocity or pressure of domain wall in the direction of electron flow. The domain wall pressure generating magnetization changes with increasing current density occurs. To that end, the simulation research was done in order to obtain the effect of the injection of electric current to the magnetization of the material. This phenomenon is simulated by modeling the material into the 3D geometry. The greater the current density is given the domain wall velocity or pressure on the nanowire faster so that the magnetization process is also faster. Changes in the velocity of the fastest domain wall is obtained when the material is injected with a current density as well as M-t get a graph showing oscillation pattern that is denser when the current is increased. Furthermore, the total energy analysis with variations in size diameter of 10 nm, 20 nm and 30 nm. The results show that with increasing diameter, total energy tends to increase. Keywords: spin transfer torque, La0.7Sr0.3MnO3, magnetisation, domain wall, ferromagnetic